1992
DOI: 10.1159/000247497
|View full text |Cite
|
Sign up to set email alerts
|

Topical Alpha-lnterferon Ointment with Dimethyl Sulfoxide in the Treatment of Recurrent Genital Herpes simplex

Abstract: The recent in vivo appearance of acyclovir-resistant strains of herpes simplex virus stresses the need for new therapeutic agents to combat this common virus. Topical interferon preparations may help fill this void. In the present study dimethyl sulfoxide was combined with α-interferon in an ointment base to increase percutaneous penetration. In this double-blind, placebo-controlled trial, patients with recurrent genital herpes simplex using the topical α-interferon preparation had a more rapid cessation of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…After healing of an infection caused by a TK-negative drug-resistant HSV strain and stopping antiviral therapy, recurrences are most often associated with a drugsensitive strain, although some cases of spontaneous recurrences of ACV-resistant viruses have been reported (1,78,100,113,125,126,142,146,152,153,178,201,205,232,246). Laboratory diagnosis of ACV resistance is required to guide clinicians toward different treatment options in cases of therapy failure.…”
Section: Laboratory Diagnosis Of Antiviral Drug Resistancementioning
confidence: 99%
“…After healing of an infection caused by a TK-negative drug-resistant HSV strain and stopping antiviral therapy, recurrences are most often associated with a drugsensitive strain, although some cases of spontaneous recurrences of ACV-resistant viruses have been reported (1,78,100,113,125,126,142,146,152,153,178,201,205,232,246). Laboratory diagnosis of ACV resistance is required to guide clinicians toward different treatment options in cases of therapy failure.…”
Section: Laboratory Diagnosis Of Antiviral Drug Resistancementioning
confidence: 99%
“…Además, se ha descrito que ICP27 (otro gen temprano) de VHS-1 tiene una función antagónica en la vía de señalización de interferones tipo-I 94 (Figura 2, panel izquierdo). Consistente con la importancia de los interferones de tipo I en el control de VHS, el tratamiento de pacientes con reactivaciones virales genitales frecuentes con IFN-α tópico, reduce la diseminación viral, así como la frecuencia de las reactivaciones 95 . Recientemente, se ha demostrado que Las glicoproteínas virales gD y gJ inhiben vías de señalización que conducen a la apoptosis celular mediada por Fas-FasL; (2 y 3) ICP27 en cambio interfiere con la vía de señalización antiviral activada por interferones (IFNR: receptor de interferón) e inhibe la expresión de MHC-I de superficie en las células infectadas a través del bloqueo de la proteína TAP; (4) Las proteínas γ34.5 y U s 11 inhiben la activación de la proteína quinasa R (PKR), la cual comúnmente fosforila al factor de inicio de la traducción 2A (eIF2A) para bloquear la traducción de proteínas en células infectadas; (5) La proteína viral vhs también inhibe la traducción de proteínas del hospedero, a través de la degradación de ARN mensajeros; (6) La proteína temprana ICP0 bloquea el factor de transcripción IRF3, el cual es necesario para la expresión de interferones y la respuesta anti-viral de la célula; (7) Finalmente, VHS-2 bloquea la síntesis y secreción de SLPI por un mecanismo aún desconocido.…”
Section: Evasión De La Respuesta Inmune Innataunclassified
“…105 Topical interferon alfa, in gel, cream, and ointment formulations at various concentrations and dosing schedules, has also been studied in a number of large, double-blind, placebo-controlled trials for the treatment of genital herpes. [107][108][109][110][111][112][113][114][115] With the exception of one study, 115 topical interferon alfa has been shown to be more effective than placebo in the treatment of primary [107][108][109] and recurrent [110][111][112][113][114] genital herpes. Interferon beta cream has also been shown to be effective in preventing recurrences of genital herpes in placebo-controlled studies.…”
Section: Herpes Simples Virusmentioning
confidence: 99%
“…Topical interferon alfa may be useful for infrequent recurrences, 110 active episodes, 114 or as an adjunct to reduce acyclovir-resistant strains of herpes simplex virus. 112 In addition, there may be a role for topical interferon alfa as an alternative to acyclovir for patients whose recurrence frequency rate does not warrant chronic oral acyclovir suppression 114 or for patients who do not want to take oral acyclovir. 112 …”
Section: Herpes Simples Virusmentioning
confidence: 99%
See 1 more Smart Citation